Flex your knowledge, play like a reflex: an UNO-inspired card game for anatomy education - Maran, Akil Indiya Mani; Suppiah, Lathigasree; Ganesan, Hematarsini; Hassan, Sarah Hassan Mohammad Muzaffar; Abas, Razif (Penerbit Universiti Sains Malaysia, 2025)
Learning anatomy can often be a daunting task due to the vast amount of information and memorisation involved. We introduce An UNO in Anatomy, an anatomy-themed card game designed to make learning anatomy more engaging and accessible. This game adapts the mechanics of the popular UNO card game, incorporating anatomical knowledge into each card’s design. Through action cards, wild cards, and anatomy-related challenges, this educational tool encourages players to think critically about human anatomy while having fun. This article presents the game concept, its potential educational impact, and suggestions for future development to improve learning outcomes.